PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI KELAS VIII SMPN 1 HILIRAN GUMANTI - Aziza, Desi (Jurnal Edukasi dan Penelitian Matematika, 2023)
The primary abilties that students ought to have after mastering mathematicsi are undesrtainding oif mathematical concepts. But, in fact, the knowledge of mathematical concepts in magnificence VIII students of SMPN 1 Hiliran Gumanti remains relatively low, due to the fact they have now not been actively concerned inside the mastering system. To conquer this problem, efforts had been made to use the problem based learning (PBL) model. The reason of this have a look at changed into to investigate and examine whether the understaniding of mathematical concepts of students who studied with the PBL version was higher than those who studied with conventional learning models and described the development of college students' understaniding of mathematical concepts so long as the PBL model changed into applied. The form of research used is descriptive research and quasy experiment with a nonequivalent posttest-only control group  design. The studies populace turned into elegance VIII college students of SMPN 1 Hiliran Gumanti inside the 2022/2023 educational year. The research devices used were quizzes at each assembly and a final check of knowledge mathematical concepts to compare students' understianding of mathematical concepts in the experimental elegance and the manipulate elegance. Based on the results of the quiz analysis at each meeting, the development of students' understanding of mathematical concepts generally increased and based on the analysis with a significance level of 0.05 obtained P-value = 0.041, meaning that P-value < ? so reject H0. This shows that the understanding of mathematical concepts of students who study with the PBL model is better than those who learn with conventional learning models. Keywords – Mathematical Concept Understanding, Problem Bsaed Learning Models, Conventional Learning Models